High-current stressing of organic light-emitting diodes with different electron-transport materials. (April 2017) - Liu, L.; Li, S.; Zhou, Y.M.; Liu, L.Y.; Cao, X.A.
Abstract: We conducted accelerated reliability tests of electron-only devices (EODs) and organic light-emitting diodes (OLEDs) differing only in their electron-transport material (ETM). High current stressing of EODs at 50 mA/cm 2 showed that Bphen Alq3 > TPBi > TAZ in terms of intrinsic material stability. In addition, the lowest unoccupied molecular orbital (LUMO) level and electron mobility have been identified as two other key material factors affecting the degradation rate of OLEDs. TAZ has a low electron mobility, a LUMO level misaligned with the Fermi level of the cathode, and poor material stability, leading to extremely poor reliability of devices with a TAZ electron-transport layer (ETL). In contrast, the OLED with a Bphen ETL exhibited more stable operation and a 76 × longer luminance lifetime. Due to its relatively high electron mobility and good stability as well as perfect energy level alignment with the cathode, Bphen has proven to be the most desirable ETM from the standpoint of OLED reliability. Highlights: Three key factors associated with ETM affecting the OLED reliability were identified. OLEDs with a TAZ electron-transport layer exhibited extremely poor reliability. OLEDs with a Bphen electron-transport layer had a 76 × longer luminance lifetime. Bphen has proven to be the most desirable ETM from the standpoint of OLED reliability.